Kedudukan Surat Penerimaan Pemberitahuan Perubahan Data Yayasan sebagai Objek Sengketa di Peradilan Tata Usaha Negara - Jenifer Beatrix Renjaan; Rasji Rasji (Syntax Literate, 2023)
In accordance with the principle of independent judicial power itself, among others, must be manifested in the independence of judges in examining and deciding the cases they face, the judge's consideration is one of the most important aspects in determining the realization of the value of a judge's decision that contains justice (ex aequo et bono) and contains legal certainty, in addition to containing benefits for the parties concerned so that this judge's consideration must be addressed with Meticulous, kind, and meticulous.